Aortic disease: thoracic endovascular aortic repair. Issue 8 (12th February 2015) - Bicknell, Colin; Powell, Janet T
Abstract : Following the first reported case of thoracic endovascular aortic repair (TEVAR) in 1987, there has been rapid technological development and widespread uptake of this approach for thoracic aortic disease. TEVAR has particular advantages for acute thoracic syndromes and there is continuing development of TEVAR for use in the elective situation. This is still a young technology and many unknowns remain, including long-term outcomes and the relative advantages and disadvantages versus both conservative treatment and open surgical repair. The current uses of TEVAR in the treatment of aortic dissection, thoracic aortic aneurysm, penetrating aortic ulcer and trauma are discussed.